Professional Preparation of Master Course Students in the Process of Pedagogical Practice - Shorobura, Inna; Mashkina, Liudmyla (Pedagogical Discourse, 2015)
The article deals with clearing out organization-methodological bases of professional preparation of master course students in the process of pedagogical practice by the specialities «Primary Education», «Pre-School Education», «Music Art». It is mentioned that the practice of the master course students is considered to be an important component of professional preparation of the future teachers of higher educational establishments, it is directed to consolidation and realization in specially created conditions of the received by master course students subject, psychologic-pedagogical, scientific-methodological knowledge, necessary for their future activity, as well as the means of creative development and self-development of master students of pedagogical education, forming professionally important qualities and readiness to innovative activity. Besides, the article also reveals basic principles and functions of practice. In particular, the attention is concentrated on such functions as: adaptational, educational, upbringing, developing and diagnostic. The essence and the main clauses of organization of on-the-job and assistant practice have been studied. The attention is concentrated on such trends of practical preparation as: acquaintance with the activity of graduate chairs, supervision of scientific-research activity of students, supervision of practice in general educational and pre-school educational establishments, observation and conducting lessons, educational measures. The main components of assistant practice and the parameters of the future teachers’ competence have been reflected in the article: scientific-theoretical preparation, methodological, psychologic-pedagogical. The key trends of the practice supervision, peculiarities of evaluation and consulting during the preparation to its conducting have been offered. The experience of practice organization of the master course students of Khmelnytskyi Humanitarian-Pedagogical Academy, where the specialists’ preparation is conducted according to the 4 education-qualificational levels: junior specialist, bachelor, specialist, magister, has been used in the article.